Pregnancy exercise with breathing exercise on changes in hemoglobin levels in anemic pregnant women - Ruwayda Ruwayda; Nurmisih Nurmisih (Jurnal Kesehatan Ibu dan Anak, 2021)
Low hemoglobin levels in pregnant women will cause various complications for the mother and fetus. Pregnancy exercise is an exercise that prepares pregnant women physically and mentally for labor.  The purpose study was to see the difference between pregnancy exercise to the combination of pregnancy exercise and breathing exercise to the change in hemoglobin levels in anemic pregnant women.  This study was a quasi-experimental study with a nonrandomized design pretest and posttest with control group design aimed at analyzing the effect of pregnancy exercise on hemoglobin levels of pregnant women. The location of the study was conducted at Putri Ayu Public Health Center, Jambi, Indonesia in 2018. Samples were taken by purposive sampling technique as many as 30 people were divided into control and treatment groups. The independent t-test showed that there was increasing level of hemoglobin level of pregnant women who exercise with breathing techniques (t=0.288; df=28; p-value=0.776; mean=0.0667; SE=0.23161; 95%CI= (-4077)-0.54110) and exercises without breathing techniques (t=0.288; df=19.422; p-value=0.777; mean=0.0667; SE=0.23161; 95%CI= (-4174)-0.55073).  The dependent t-test shows that pregnancy exercise with breathing exercise was increasing hemoglobin level more than pregnancy exercise without breathing exercise (p-value=0.010). Pregnancy exercise with breathing exercise was more effective to increase the hemoglobin level in anemic pregnant women.